Satellite Cloud Network: A Satellite Network Architecture Based on Cloud-Network Integration - Zhigang YU; Wenhui DING; Zhou LU; Xu FENG; Jixing GAO (天地一体化信息网络)
With the public land mobile communication network transitioning from the 5G era where information flows freely to the 6G era where everything is interconnected, satellite networks have become a hot development topic all around the world.At the same time, with the improvement of satellite on-board computing capabilities and the integration of computing and satellite networks, cloud network integration has become a new development trend.On the basis of a brief introduction to the current development status of satellite networks and satellite computing, the development roadmap of satellite network development architecture was summarized.Then, a satellite network architecture based on cloud-network integration (i.e.satellite cloud network) was proposed, and the advantages of satellite cloud network architecture from five aspects: computing driven communication enhancement, computing driven network enhancement were analyzed, computing driven service enhancement, computing driven control enhancement, and computing driven management enhancement.